2017
DOI: 10.17098/amj.364164
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Count as Chronic Inflammation Markers in Type 2 Diabetes Patients

Abstract: ÖzAmaç: Epidemiyolojik araştırmalar periferik kandaki lökosit sayısı ile Tip 2 Diyabetes Mellitus (T2DM) arasında ilişki bulunduğunu göstermesine rağmen bu ilişki sistematik olarak incelenmemiştir. Bu çalışmada, T2DM tanısı olan hastaların (T2DM(+)) lökosit sayımı ve biyokimya tetkik sonuçlarının diyabeti olmayan hastaların (T2DM(-)) sonuçlarıyla karşılaştırılması amaçlanmıştır. Materyal ve Metot: Çalışmaya; 02.02.2015-30.09.2015 tarihleri arasında Dışkapı Yıldırım Beyazıt Eğitim ve Araştırma Hastanesi Aile He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The leukocyte count, which can be rapidly measured with a hemogram test, is frequently used in daily practice and is a well-known inflammation indicator [ 26 ]. Although Yang et al found an increase in the WBC count after successful PTX in patients with hyperparathyroidism, this was not at a statistically significant level.…”
Section: Discussionmentioning
confidence: 99%
“…The leukocyte count, which can be rapidly measured with a hemogram test, is frequently used in daily practice and is a well-known inflammation indicator [ 26 ]. Although Yang et al found an increase in the WBC count after successful PTX in patients with hyperparathyroidism, this was not at a statistically significant level.…”
Section: Discussionmentioning
confidence: 99%